Peningkatan Kualitas dan Nilai Jual Hortikultura Melalui Pelatihan Teknik Pengemasan di Desa Segorogunung. - Virgita Sari Yudhoningrum; Dana Pasa Bintang Sakti Permana; Steven Immanuel Pratama Manurung; Tira Nasywaa Aurelia; Wanda Aniisa Rahmajati; Syifa Yusriyah Destriyani; Muhammad Iqbal Rabbani; Tara Adista Yanuari; Wahyu Indraswari; Joko Ariyanto; Nurfitria Insani Hanifa (Jurnal Riset Multidisiplin Edukasi, 2026)
Segorogunung Village is located on the slopes of Mount Lawu, which provides suitable natural conditions for agricultural activities. The people of Segorogunung Village take advantage of these conditions by growing horticultural products, especially vegetables. Vegetables are known to be perishable and do not last long. This results in losses for farmers, so a solution is needed to overcome this problem. One effort that can be made is through proper post-harvest handling, such as packaging. The purpose of public service is to educate society on how to package horticultural products so that they are durable and have a higher selling value. Implementing the method of implementation, starting from preparation, training, and evaluation of activities properly. The public service activity carried out in February 2026 was well-executed, as evidenced by the audience's understanding and ability to practice reliable packaging. Materials and tools such as plastic wrapping, foam trays, polypropylene (PP) plastic, “Fresh Vegetable” isolation, and labels fulfilled packaging and modern market standards. It is hoped that this will have an impact on economic sustainability. The expected long-term impact is a reduction in crop losses and an increase in farmers’ profits.